Duty ratio modulation direct torque control of brushless doubly-fed machines. (2nd October 2017) - Bing, Li; Shi, Liu; Teng, Long; Jia, Zhang
ABSTRACT: For the brushless doubly-fed machine (BDFM), traditional direct torque control (DTC) has many problems such as big output torque ripple and uncertain inverter switch frequency. Based on the analysis of traditional DTC, this paper proposed a new torque control which applied duty ratio modulation into direct torque control. This new control method can decrease the torque ripple effectively by adding zero voltage in each control cycle. According to the brushless BDFM state equation and the prediction of torque, flux linkage in the next moment and the theory of electromagnetic torque equals to referenced value at the instant moment in one control cycle, torque ripple can be decreased. Through theoretical analysis and experiments, the proposed control method has all advantages of traditional direct torque control and can decrease torque ripple and flux linkage ripple, which can optimize the performance of direct torque control.